Near infrared reflectance measurement of nitrogen faecal losses. Issue 6 (June 1992) - Benini, L; Caliari, S; Bonfante, F; Guidi, G C; Brentegani, M T; Castellani, G; Sembenini, C; Bardelli, E; Vantini, I
Abstract : Chemical methods of measuring nitrogen in stools are complex, unpleasant, and therefore rarely performed. Recently, near infrared reflectance (NIRA) has been suggested for stool analysis. The aim of this study was to evaluate the possible application of this method in routine faecal nitrogen measurement. Nitrogen concentration and daily output were measured in the stools of 83 patients using NIRA and, for comparison, the Kjeldahl method. Nitrogen concentration and output ranged between 0.4-2.72 g% and 0.45-8.96 g/day respectively. Correlation coefficients (r), of 0.89 and 0.97 were found between the two methods for concentration and output respectively, and similar values were found in patients on enteral nutrition. Repeated measurements from the same stool collection, requiring only a few minutes, allowed homogenisation to be avoided. NIRA seems to be an easy, fast, and reliable alternative to chemical assays of nitrogen measurement in the management of patients with digestive disorders.